Military in politics ; Blood bank ; Leaps and bounds [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Tackles retired military men and entertainers joining politics; commercial blood bans as inadequate and defective sources; and Julie Ilarde's training for thythmic gymnastics.
Military in politics (16 min.) -- Blood bank (15 min.) -- Leaps and bounds (16 min.)
VHS
Keywords: Retired military personnel -- Interviews -- Philippines; Blood banks -- Philippines; Gymnastics for women -- Coaching -- Philippines; Rhythmic gymnastics -- Philippines; Philippines -- Politics and government -- 1992-.